Risk factors for the development of striae gravidarum - Osman, Hibah (Elsevier, 2007)
OBJECTIVE: The purpose of this study was to identify risk factors associated with striae gravidarum (SG). STUDY DESIGN: A cross-sectional study of 112 primiparous women delivering at a private teaching hospital was conducted. Participants were assessed during the immediate postpartum period for evidence of SG. Presence and severity of SG were compared to characteristics of women using t tests and Chi-square tests. RESULTS: Sixty percent of the study participants had developed SG. Women who developed SG were significantly younger (26.5 ± 4.5 vs 30.5 ± 4.6; P < .001) and had gained significantly more weight during pregnancy (15.6 ± 3.9 vs 38.4 kg ± 2.7; P < .001). Birthweight (BW), gestational age at delivery, and family history of SG were associated with moderate/severe SG. CONCLUSION: Maternal age and weight gain during pregnancy are associated with SG. BW, family history of SG, and gestational age at delivery are associated with moderate/severe SG.